2002
DOI: 10.1590/s1517-74912002000400008
|View full text |Cite
|
Sign up to set email alerts
|

Cervical shaping in curved root canals: comparison of the efficiency of two endodontic instruments

Abstract: The aim of this study was to determine the removal of dentin produced by number 25 (0.08) Flare files (Quantec Flare Series, Analytic Endodontics, Glendora, California, USA) and number 1 e 2 Gates-Glidden burs (Dentsply - Maillefer, Ballaigues, Switzerland), in the mesio-buccal and mesio-lingual root canals, respectively, of extracted human permanent inferior molars, by means of measuring the width of dentinal walls prior and after instrumentation. The obtained values were compared. Due to the multiple analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The first rotary instruments used for cervical preflaring were Gates Glidden burs (7), which are still commonly used during endodontic procedures. The diameter of the Gates Glidden bur #2 (0.70 mm) is generally considered safe for the cervical preflaring of mesial canals of mandibular molars (8), but it cannot completely remov cervical interferences, particularly below the cementoenamel junction (9). Isom et al (10) studied the anti-curvature motion using Gates Glidden burs #2 and #3 and found significant dentin removal at the furcal aspect of the root canal (danger zone).…”
Section: Introductionmentioning
confidence: 99%
“…The first rotary instruments used for cervical preflaring were Gates Glidden burs (7), which are still commonly used during endodontic procedures. The diameter of the Gates Glidden bur #2 (0.70 mm) is generally considered safe for the cervical preflaring of mesial canals of mandibular molars (8), but it cannot completely remov cervical interferences, particularly below the cementoenamel junction (9). Isom et al (10) studied the anti-curvature motion using Gates Glidden burs #2 and #3 and found significant dentin removal at the furcal aspect of the root canal (danger zone).…”
Section: Introductionmentioning
confidence: 99%
“…Although GG drills are conventionally and one of the most commonly used instruments for cervical preflaring, these have an aggressive cutting action and do not have a taper and tend to cut more toward the furcal wall. [8] It has been shown that even anticurvature filing motion does not reduce the risk of perforation by GG drills. [7] However, studies have shown that if used with caution they can be an inexpensive tool for coronal preflaring.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they tend to cut more dentin in the furcal region (danger zone) thus compromising tooth integrity. [7,8] Today, most of the Ni-Ti rotary systems offer orifice openers and shapers for preflaring of the canals. Quite popular among these, the auxiliary shaping Ni-Ti file Protaper Sx, offer advantages such as superelasticity, lesser chance of canal transportation and strip perforation when compared to the stainless steel GG drills.…”
Section: Efficacy Of La Axxess Burs Gates Glidden Drills and Protapementioning
confidence: 99%
“…While the literature agrees on the influence of heat treatment, more studies are necessary to understand the role of metal mass on torsional resistance [12,13]. Some articles state that the main influence of mass on torsional resistance is related to the total amount of mass, while other studies emphasize the importance of mass distribution along the instrument [14,15]. At present, the method of choice for testing static rotational resistance is evaluating instruments as described by the International Organization for Standardization (ISO) 3630-1 [16].…”
Section: Introductionmentioning
confidence: 99%